In vivo molecular imaging of peripheral amyloidosis using heparin-binding peptides - Wall, Jonathan S; Richey, Tina; Stuckey, Alan; Donnell, Robert; Macy, Sallie; Martin, Emily B; Williams, Angela; Higuchi, Keiichi; Kennel, Stephen J (Proceedings of the National Academy of Sciences - PNAS, 2011)
Heparan sulfate proteoglycans (HSPGs) are ubiquitous components of pathologic amyloid deposits in the organs of patients with disorders such as Alzheimer's disease or systemic light chain (AL) or reactive (AA) amyloidosis. Molecular imaging methods for early detection are limited and generally unavailable outside the United Kingdom. Therefore, there is an urgent need to develop novel, specific amyloidophilic radiotracers for imaging to assist in diagnosis, prognostication, and monitoring response to therapy. Amyloid-associated HSPG can be differentiated from HSPG found in surrounding healthy cells and tissues by the preferential binding of certain HS-reactive single chain variable fragments and therefore, represents a biomarker that can be targeted specifically with appropriate reagents. Using a murine model of AA amyloidosis, we have examined the in vivo amyloid reactivity of seven heparin-binding peptides by using single photon emission and X-ray computed tomographic imaging, microautoradiography, and tissue biodistribution measurements. All of the peptides bound amyloid deposits within 1 h post-injection, but the extent of the reactivity differed widely, which was evidenced by image quality and grain density in autoradiographs. One radiolabeled peptide bound specifically to murine AA amyloid in the liver, spleen, kidney, adrenal, heart, and pancreas with such avidity that it was observed in single photon emission tomography images as late as 24 h post-injection. In addition, a biotinylated form of this peptide was shown histochemically to bind human AA, ALκ, ALλ, transthyretin amyloidosis (ATTR), and Aβ amyloid deposits in tissue sections. These basic heparin-binding peptides recognize murine and human amyloid deposits in both in vivo and ex vivo tissues and therefore, have potential as radiotracers for the noninvasive molecular imaging of amyloid deposits in situ.